The Influence of Accounting Knowledge and Professional Ethics on Accounting Students' Perception at the University of Islamic North Sumatra and the Muslim Nusantara Al-Washliyah University Regarding Creative Accounting Practices - Wahidah, Nur; Simbolon, Ramadona; Lubis, Farida Khairani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Creative accounting is a financial reporting method in which managers participate for personal gain. Accounting knowledge and ethics can influence accounting students' views on creative accounting cases. Accounting students are prospective accountants who have an important role in reducing creative accounting practices, so it is very important to know the opinions of accounting students about creative accounting practices. The purpose of this study was to examine the effect of accounting knowledge and professional ethics on the perceptions of accounting students at the Islamic University of North Sumatra and the Muslim University of Al-Washliyah regarding creative accounting practices. This study uses a quantitative method, the type of data used is primary data with data collection carried out through a questionnaire using a Likert scale distributed to 73 accounting student respondents at UISU and UMN Al-Washliyah. Based on the results of the SPSS 22 test, the results of the study showed that accounting knowledge did not affect the perceptions of accounting students at the Islamic University of North Sumatra and the Muslim University of Al-Washliyah regarding creative accounting practices, knowledge of professional ethics had a positive effect on the perceptions of accounting students at the Islamic University of North Sumatra and the Muslim University of Al-Washliyah regarding creative accounting practices, accounting knowledge and professional ethics simultaneously influenced the perceptions of accounting students at the Islamic University of North Sumatra and the Muslim University of Al-Washliyah regarding creative accounting practices.